Quinolines from the cyclocondensation of isatoic anhydride with ethyl acetoacetate: preparation of ethyl 4-hydroxy-2-methylquinoline-3-carboxylate and derivatives - Jentsch, Nicholas G.; Hume, Jared D.; Crull, Emily B.; Beauti, Samer M.; Pham, Amy H.; Pigza, Julie A.; Kessl, Jacques J.; Donahue, Matthew G. (Beilstein Journal of Organic Chemistry, 2018)
A convenient two-step synthesis of ethyl 4-hydroxy-2-methylquinoline-3-carboxylate derivatives has been developed starting from commercially available 2-aminobenzoic acids. In step 1, the anthranilic acids are smoothly converted to isatoic anhydrides using solid triphosgene in THF. In step 2, the anhydride electrophiles are reacted with the sodium enolate of ethyl acetoacetate, generated from sodium hydroxide, in warm N,N-dimethylacetamide resulting in the formation of substituted quinolines. A degradation–build-up strategy of the ethyl ester at the 3-position allowed for the construction of the α-hydroxyacetic acid residue required for the synthesis of key arylquinolines involved in an HIV integrase project.
Keywords: cyclodehydration; HIV integrase; isatoic anhydride; masked acyl cyanide; quinoline